The Role of Kiai in Building the Character of Students in Islamic Boarding Schools - Nurhakim, Nova (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The issue of character education has become increasingly prominent, especially amidst the current moral crisis. Islamic boarding schools (pesantren) are expected to serve as alternative institutions that can be studied and exemplified in implementing moral and character education. Beyond being a transmitter of knowledge, skills, and values, the kiai (Islamic religious leader) also plays a vital role as a role model for the students (santri). This research employed a descriptive qualitative method, using data collected through interviews, field observations, and document studies. The findings indicate that the kiai plays a significant role in shaping students’ character. The roles and resulting character development include: (1) the kiai as a role model (uswah hasanah), which fosters values such as honesty, responsibility, discipline, humility (tawadhu’), patience, and sincerity; (2) as a moral and spiritual educator through sermons, classical Islamic book studies (kitab kuning), and daily interactions; (3) as a guide and caretaker who provides personal attention, encouraging openness and receptiveness among students; (4) as a preserver of Islamic traditions, promoting peaceful, open-minded, and tolerant personalities; (5) as a motivator and inspirator, helping shape strong and resilient character; (6) as a disciplinarian and builder of independence, forming firm, courageous, and self-reliant individuals; and (7) as a cultivator of future leaders—faithful, knowledgeable, noble in character, and ready to contribute to the community and nation.